Sub-brachypterous Ricaniidae (Hemiptera: Fulgoromorpha) of Madagascar with morphological notes for these taxa - Stroiński, Adam; Gnezdilov, Vladimir M.; Bourgoin, Thierry (Zootaxa, 2011)
Four new genera of sub-brachypterous Ricaniidae are described from Madagascar. Globularica gen. nov. is established for a single species, Globularica diversicolorata sp. nov. Coniunctivena gen. nov. is established for four species: Coniunctivena antsignyensis sp. nov., C. epaulettea sp. nov. (type species), C. montuosa sp. nov., C. synavei sp. nov. Nasatus gen. nov. is established for two species: Nasatus sparsus sp. nov. (type species) and N. davidouvrardi sp. nov. Cyamosa gen. nov. is established for four species: Cyamosa adelinae sp. nov., C. camelouca sp. nov. (type species), C. pauliani sp. nov., C. splendens sp. nov. Isobium gibbosum Melichar, 1906 is redescribed and transferred from the Issidae to the Ricaniidae. Photographs, drawings and maps of distribution for all mentioned species are presented. Discussion is provided on antennal plate organs, tegminal sub-brachypterism, and female bursa copulatrix structure, for these sub-brachypterous Ricaniidae.